Vestibular and Multi-Sensory Influences Upon Self-Motion Perception and the Consequences for Human Behavior - Britton, Zelie; Arshad, Qadeer (Frontiers in Neurology, 2019)
In this manuscript, we comprehensively review both the human and animal literature regarding vestibular and multi-sensory contributions to self-motion perception. This covers the anatomical basis and how and where the signals are processed at all levels from the peripheral vestibular system to the brainstem and cerebellum and finally to the cortex. Further, we consider how and where these vestibular signals are integrated with other sensory cues to facilitate self-motion perception. We conclude by demonstrating the wide-ranging influences of the vestibular system and self-motion perception upon behavior, namely eye movement, postural control and spatial awareness as well as new discoveries that such perception can impact upon numerical cognition, human affect and bodily self-consciousness.